NINDS at 50 : Celebrating 50 Years of Brain Research. - Rowland, Lewis P. (Demos Medical Pub., LLC, 2003)
NINDS has been one of the most powerful motors that pulled and pushed the rise of modern neuroscience. This book was written in celebration of the fiftieth anniversary of the institute. Its history and the history of neurology and neuroscience are essentially one. Well written, and lavishly accompanied by photographs that span the last half-century, this book will be a welcome addition to the library of everyone in brain research and the clinical neurosciences. The first half is a history of the Institute, starting with the enabling legislation and concentrating on the people who made NINDS a.